AIDS and masculinity in the African city : privilege, inequality, and modern manhood - Wyrod, Robert (University of California Press, 2016)
"AIDS has been a devastating plague in much of Sub-Saharan Africa, yet the long-term implications for gender and sexuality are just emerging. This book examines how AIDS has altered the ways masculinity is lived in Uganda, a country known as Africa's great AIDS success story. Based on extensive ethnographic research in an urban slum community called Bwaise, this book reveals the persistence of masculine privilege in the age of AIDS and the implications such privilege has for men's and women's health and wellbeing in Uganda and beyond"--Provided by publisher.